Carotid Artery Stenosis and Ischemic Strokes in Patients with Giant Cell Arteritis - Oerding, Clemens; Uhlmann, Frank; Wollmann, Johannes; Kaden, Ingmar; Wohlfarth, Kai (TH Open, 2022)
Purpose Ischemic stroke is a relatively rare complication of giant cell arteritis often accompanied by vessel stenosis. Our purpose was to compare the location of internal carotid artery stenosis in GCA patients by performing a literature review suggesting a specific and characteristic pattern.Methods We performed a PubMed research including all articles and cited articles reporting cases and case series about giant cell arteritis patients with internal carotid artery stenosis and ischemic strokes.Results In this case series 39 cases were included. We found a clear tendency of giant cell arteritis-related stenosis to be in the intracranial segments (35/39 (89.7%)). Only in 8/39 (20.5%) patients there was further involvement of extracranial segments. Many cases (27/39 [69.2%]) showed a bilateral involvement.Discussion This literature review reveals a specific pattern of internal carotid artery involvement in patients with giant cell arteritis and ischemic strokes. To our knowledge this pattern has not been reported as a sign strongly pointing toward giant cell arteritis before. We have not found case reports mentioning other common types of vasculitis reporting this involvement pattern.Conclusion Internal carotid artery stenosis and ischemic stroke is a rare complication in patients with giant cell arteritis. Considering the characteristic features of bilateral distal internal carotid artery stenosis giant cell arteritis should be suspected which potentially leads to an early diagnosis and immunotherapy.
Keywords: vasculopathy; stenosis; stroke; vessel wall enhancement; internal carotid artery; vasculitis; imaging; temporal artery biopsy; giant cell arteritis; Horton disease